2001
DOI: 10.1142/s0217979201005222
|View full text |Cite
|
Sign up to set email alerts
|

Two Dimensional Flow of an Esf: Experiment, Cfd, Bingham Plastic Analysis

Abstract: The two dimensional flow of an electrorheological fluid in a concentric cylinder, Couette type apparatus is investigated at different inter-plate speeds, voltages and axial pressure gradients. Test results at low, but realistic, loading conditions correlate with Bingham plastic computer fluid dynamics (CFD) package predictions, at each field strength. The package had been pre verified against an analytical solution for the same flow field. In all cases the liquid is taken to be isothermal. Indications are that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Here the speeds were chosen to be within the range used in Kordonski and Gorodkin (1995). However, in earlier work (Atkin et al (1994), Ellam et al (2000), Atkin et al (2000) and Bullough et al (2001)) where higher speeds were used, very good agreement was found between this theory and the results from CFD. This indicates that care has to be taken when replacing the cylindrical geometry by two parallel flat plates.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Here the speeds were chosen to be within the range used in Kordonski and Gorodkin (1995). However, in earlier work (Atkin et al (1994), Ellam et al (2000), Atkin et al (2000) and Bullough et al (2001)) where higher speeds were used, very good agreement was found between this theory and the results from CFD. This indicates that care has to be taken when replacing the cylindrical geometry by two parallel flat plates.…”
Section: Discussionmentioning
confidence: 97%
“…When the operating parameters are such that the values of a and G lie inside the ellipse a 2 = 2 e þ G 2 =ð2 e =hÞ 2 ¼ 1 no axial flow can occur and the shaft cannot rotate. The main results are given below (see Atkin et al (1994) and Bullough et al (2001) Section 2, for further details).…”
Section: Theoretical Analysis: Bingham Plastic Flat Plate Theorymentioning
confidence: 99%